José Román de la Torre y Peralta: una carrera literaria en la Sevilla del Bajo Barroco - Sánchez Jiménez, Antonio; López Lorenzo, Cipriano (Santiago de Compostela: Andavira, 2022)
Analysis of José Ramón de la Torre Peralta's poetic career
Keywords: Golden Age Spanish Poetry